(untitled) (Bangladesh Journal of Medical Science, 2011)
Gummatous ulcer due to Treponematoses is quite rare in present era of potent antibiotics, increased social awareness and due to improvement in living standards of society .Better hygiene and improved medical care have contributed to containment of late benign syphilis or gummas. However, pockets of endemic treponematoses is still persisting in the underdeveloped, third world countries. Key words: Gummatous ulcer, treponematoses, antibiotics. DOI: http://dx.doi.org/10.3329/bjms.v10i3.7514 BJMS 2011; 10(3): 209-210